Functional properties and structural characterization of rice δ1-pyrroline-5-carboxylate reductase - Forlani, Giuseppe; Bertazzini, Michele; Zarattini, Marco; Funck, Dietmar; Ruszkowski, Milosz; Nocek, Bogusław (Frontiers in Plant Science, 2015)
The majority of plant species accumulate high intracellular levels of proline to cope with hyperosmotic stress conditions. Proline synthesis from glutamate is tightly regulated at both the transcriptional and the translational levels, yet little is known about the mechanisms for post-translational regulation of the enzymatic activities involved. The gene coding in rice (Oryza sativa L.) for δ1-pyrroline-5-carboxylate (P5C) reductase, the enzyme that catalyzes the second and final step in this pathway, was isolated and expressed in E. coli. The structural and functional properties of the affinity-purified protein were characterized. As for most species, rice P5C reductase was able to use in vitro either NADH or NADPH as the electron donor. However, strikingly different effects of cations and anions were found depending on the pyridine nucleotide used, namely inhibition of NADH-dependent activity and stimulation of NADPH-dependent activity. Moreover, physiological concentrations of proline and NADP+ were strongly inhibitory for the NADH-dependent reaction, whereas the NADPH-dependent activity was mildly affected. Our results suggest that only NADPH may be used in vivo and that stress-dependent variations in ion homeostasis and NADPH/NADP+ ratio could modulate enzyme activity, being functional in promoting proline accumulation and potentially also adjusting NADPH consumption during the defense against hyperosmotic stress. The apparent molecular weight of the native protein observed in size exclusion chromatography indicated a high oligomerization state. We also report the first crystal structure of a plant P5C reductase at 3.40-Å resolution, showing a decameric quaternary assembly. Based on the structure, it was possible to identify dynamic structural differences among rice, human and bacterial enzymes.